A hybrid prevention method for eavesdropping attack by link spoofing in software-defined Internet of Things controllers. (November 2017) - Nguyen, Tri-Hai; Yoo, Myungsik
With the rapid growth of Internet of Things technologies, the management and control of Internet of Things networks face remarkable challenges. As such, software-defined networking, which decouples the control layer from data layer, results in various advantages. An association of software-defined networking and Internet of Things, which is referred to as software-defined Internet of Things, provides a robust platform to improve the management and control abilities of Internet of Things networks. However, these benefits have resulted in an increase in the number of malicious attacks on logically centralized controllers. For that reason, we have performed a specific vulnerability analysis in the link service, where the controller learns network topology through discovering every link between switches. In addition, we demonstrate link spoofing attacks on the link service, and discuss a hybrid countermeasure to address this security problem.